Entrepreneurial Competency and its Characteristics in Business Success - Kaur, Hardeep; Bains, Anupama (Gyan Management Journal, 2015)
Competency as a concept has evolved over the years. Its potential isto bring about efficiency in business operations. The objective of this study is to understand the concept of entrepreneurial competency and aims to identify the characteristics of entrepreneurial competency required for success of business. Entrepreneurial characteristics play an important role in running the business effectively and efficiently, in order to garner success of an enterprise in terms of resources and development ..The research found that the characteristics that play a significant role in business success are psychological factors i.e. need to achieve, risk taking, self confidence and non-psychological factors i.e. human capital and social capital and personal characteristics such as education, training, motivation.
Keywords: Competency; Entrepreneur; Entrepreneurial Competency; Business